Band Alignment Engineering Towards High Efficiency Carbon‐Based Inorganic Planar CsPbIBr2 Perovskite Solar Cells. Issue 10 (3rd May 2019) - Zhu, Weidong; Zhang, Zeyang; Chai, Wenming; Zhang, Qianni; Chen, Dazheng; Lin, Zhenhua; Chang, Jingjing; Zhang, Jincheng; Zhang, Chunfu; Hao, Yue
Abstract: Perovskite CsPbIBr2 is attracting ever‐increasing attention for carbon‐based, all‐inorganic solar cells, owing to its well‐balanced band gap and stability features. However, significant interfacial recombination of charge carriers in solar cells fabricated with this active layer, which is intrinsically associated with the unwanted conduction band misalignment between CsPbIBr2 and the commonly used TiO2 electron transport layer, has limited power conversion efficiency (PCE) values. Herein, we demonstrate successful conduction band alignment engineering at the TiO2 /CsPbIBr2 heterojunction by modifying TiO2 with CsBr clusters. Such modification triggers a beneficial increase in the conduction band minimum (CBM) of TiO2 from −4.00 to −3.81 eV and decreases the work function from 4.11 to 3.86 eV, thus promoting favorable band alignment at the heterojunction, suppressing recombination, and improving extraction and transport of charge carriers. As a result, the carbon‐based, all‐inorganic CsPbIBr2 solar cells exhibit over 20 % enhancement in average PCE. The champion device achieves a PCE of 10.71 %, a record among pure CsPbIBr2 ‐based cells, open‐circuit voltage of 1.261 V, and excellent stability. Abstract : Efficiently aligned : Innovative CsBr modification of the TiO2 electron transport layer (ETL) leads to a carbon‐based all‐inorganic planar CsPbIBr2 perovskite solar cells with record‐high efficiency of 10.71 %. This high efficiency is attributed to favorable band alignment of the TiO2 /CsPbIBr2 heterojunction, owing to the elevated conduction band and decreased work function of the CsBr‐modified TiO2, which effectively suppresses charge recombination as well as improves extraction and transport of charge carriers.